2018
DOI: 10.1186/s12905-018-0637-6
|View full text |Cite
|
Sign up to set email alerts
|

The randomised uterine septum transsection trial (TRUST): design and protocol

Abstract: BackgroundA septate uterus is a uterine anomaly that may affect reproductive outcome, and is associated with an increased risk for miscarriage, subfertility and preterm birth. Resection of the septum is subject of debate. There is no convincing evidence concerning its effectiveness and safety. This study aims to assess whether hysteroscopic septum resection improves reproductive outcome in women with a septate uterus.Methods/designA multi-centre randomised controlled trial comparing hysteroscopic septum resect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 31 publications
0
24
0
1
Order By: Relevance
“…Likewise, the ESHRE guideline concludes that the effect of septum resection should be evaluated in randomized controlled trials and that other uterine reconstructions are not recommended. The TRUST trial (Dutch trial number: NTR 1676) is currently investigating whether hysteroscopic septum resection improves the reproductive outcome in women with a septate uterus (Rikken et al, 2018). Regarding acquired intrauterine malformations, the ESHRE and ASRM conclude that there is insufficient evidence for the removal of fibroids or adhesions (Asherman syndrome).…”
Section: Therapymentioning
confidence: 99%
“…Likewise, the ESHRE guideline concludes that the effect of septum resection should be evaluated in randomized controlled trials and that other uterine reconstructions are not recommended. The TRUST trial (Dutch trial number: NTR 1676) is currently investigating whether hysteroscopic septum resection improves the reproductive outcome in women with a septate uterus (Rikken et al, 2018). Regarding acquired intrauterine malformations, the ESHRE and ASRM conclude that there is insufficient evidence for the removal of fibroids or adhesions (Asherman syndrome).…”
Section: Therapymentioning
confidence: 99%
“…A Cochrane review published in 2017 did not identify any published randomised controlled studies assessing the efficacy in pregnancy outcomes after hysteroscopic metroplasty. The Randomised Uterine Septum Transsection Trial (TRUST) to assess whether hysteroscopic septum resection improves reproductive outcomes in women with a septate uterus and a history of (recurrent) miscarriage, subfertility or preterm birth is a multicentre study currently underway in the Netherlands, Iran and USA, with results awaited. A pilot single‐centred randomised controlled trial of hysteroscopic septal resection in women with septate uteri, history of miscarriage or preterm birth, or infertility had been proposed in the UK, but has not been feasible because of difficulty in recruiting women and clinicians to participate – a problem experienced by the authors of the TRUST trial also…”
Section: Management Optionsmentioning
confidence: 99%
“…However, a systematic review, a large cohort study, and the TRUST trial showed no benefits from hysteroscopic septum resection in infertile women in comparison to expectant management. [63][64][65] But it is possible that women treated expectantly underwent diagnostic procedures with tubal flushing for diagnosing the septum (i.e., HSG, sonohysterography, hysteroscopy). These diagnostic procedures can mask the effect of tubal flushing associated with metroplasty, when the group without surgical intervention underwent tubal flushing according to study protocols, which are focused directly on surgical procedure, but not on the associated tubal flushing.…”
Section: Diagnostic Hysteroscopy and Operative Hysteroscopymentioning
confidence: 99%